Perancangan Turbin Angin Vertikal Modifikasi Darrieus Menggunakan Geometri Airfoil Naca 2414 - Andreas; Rahmad Samosir; Medyawanti Pane (JOURNAL OF MECHANICAL ENGINEERING MANUFACTURES MATERIALS AND ENERGY, 2023)
The National Energy General Plan policy is one of the government's focuses on controlling the use of renewable energy in line with the development of the need for energy use for the community, especially in the electricity sector. Electrical energy is energy that is very important for human needs, where every human being is very dependent on electricity for their daily needs. Currently, there is a crisis of fossil resources, so renewable energy can be developed. One renewable energy that is easy to develop is a wind turbine by utilizing the energy of the wind that blows. Indonesia has started to pay attention to increasing the efficiency of electricity generation, especially wind power. The type of turbine planned is the Darrieus type vertical axis wind turbine (VAWT) using a modified NACA Airfoil 2414 geometry with variations in wind speed. At a speed of 7,61 m/s from the test results obtained the power produced by the turbine is 20,78 watts with a voltage of 11,61 Volts and an electric current of 1,79 Amperes and at 354 rpm generator rotation. from the results obtained, the higher the wind speed, the higher the rotation produced by the turbine.